Prevalence and risk factors of burnout among Lebanese community pharmacists in the era of COVID-19 pandemic: results from the first national cross-sectional survey - Dalal Youssef; Janet Youssef; Hamad Hassan; Linda Abou-Abbas (Taylor & Francis Group, 2021)
Background Community pharmacists (CPs) are increasingly facing occupational challenges as a result of the COVID-19 pandemic, putting them at high risk of burnout. This study aimed to assess the prevalence of burnout among Lebanese CPs during the COVID-19 pandemic and to identify its associated factors. Methods An online survey was conducted among Lebanese CPs between February 1st and March 30, 2021. Collected data included information on sociodemographic characteristics, exposure and work-related variables, the Copenhagen burnout inventory (CBI), and the COVID-19 threat perception scale. Prevalence of burnout was calculated. Multiple logistic regressions were performed to identify the factors associated with the three burnout domains. Results A total of 387 CPs participated in the survey. Of the total, 53.7% were females; and 43.2% were aged less than 40 years old. The prevalence of moderate-to-high personal, work-related and client-related burnout was 77.8%, 76.8, and 89.7%, respectively. Younger age, staff pharmacist, working more than 40 h per week, high perceived COVID-19 threat were associated with a moderate-to-high likelihood of burnout in all three domains. However, altruistically accepting the risks of caring for COVID-19 patients was the only variable that was associated with a lower likelihood of burnout in all three domains. Conclusion An alarming prevalence of personal, work-related and client-related burnout was revealed among Lebanese CPs. This study has many implications for practice and provides a framework for establishing policy interventions to reduce burnout levels among Lebanese CPs. Preventive strategies and interventions on individual and organizational basis are recommended.